The Perceptions of Women About Their High Experience of Using Crack Cocaine - Tractenberg, Saulo G.; Schneider, Jaluza A.; Mattos, Bernardo P. de; Bicca, Carla H. M.; Kluwe-Schiavon, Bruno; de Castro, Thiago G.; Habigzang, Luísa F.; Grassi-Oliveira, Rodrigo (Frontiers in Psychiatry, 2022)
Introduction: The aim of this study was to explore the perceptions of women about their experience in using crack cocaine, discussing their motivations for using it and the repercussions in their lives. Objective: To investigate these experiences, a qualitative exploratory study was conducted, using the inductive thematic analyses of the content. Methods: Eight female crack cocaine users took part in this study. They were assessed by a semi-structured interview, addressing the crack cocaine use experience. Four main themes emerged in the interviews: 1) crack cocaine “high” experience; 2) symptoms related to crack cocaine use; 3) circumstances of crack cocaine use; and 4) crack cocaine use consequences. Results: The main perceptions reported by the users were related to a feeling of being disconnected to the world preceded by a pleasant experience, especially during the first moments of use. They revealed that the drug fulfills a key role of coping strategy to handle with negative thoughts, emotions or life experiences. An important influence of social issues was reported in relation to the onset of crack cocaine use. Negative consequences and significant impact on their lives appeared in their reports, regarding the loss of family ties, involvement with prostitution, traumatic experiences and violence. Conclusion: Taking together all women`s perceptions suggests that beyond the positive immediate rewarding effect, the maintenance of use might be related to the dissociative experience and self-medication role, acting as negative reward by relieving of negative life experiences that, in turn, are both cause and consequence of the drug use.